Teacher's Perceptions on the Impact of Curriculum Changes on Accounting Learners’ Academic Performance - Dikgale , Selina; Chauke, Thulani (Universitas Djuanda, 2024)
This study explores teachers' perceptions regarding the impact of curriculum changes on the academic performance of accounting learners in four selected secondary schools. The ongoing curriculum changes created a state of uncertainty and bewilderment among teachers, which in turn has affected learners' academic performance. Employing a qualitative research approach aligned with interpretivism paradigms, data was gathered through semi-structured interviews. A purposive sampling technique was utilized to select 20 participants from four secondary schools, comprising principals, deputy principals, heads of departments, and teachers within the Shamavunga circuit, Mopani District, Limpopo. Thematic analysis was employed to analyze the data, with due consideration given to ethical guidelines throughout the study. The findings revealed the significant challenges teachers face in the context of accounting science due to curriculum changes. It is apparent that reluctance among certain teachers to embrace novel pedagogical approaches, alongside impediments encountered by learners such as restricted access to learning resources and time constraints, markedly hinder the academic performance of accounting learners. Furthermore, the insufficiency of teacher training concerning curriculum changes emerges as a critical factor impacting their ability to effectively convey accounting concepts to accounting learners. Consequently, this deficit in teaching proficiency directly influences learners' grasp of the subject matter, ultimately affecting their academic performance. To enhance the educational achievement of accounting learners amidst curriculum changes, it is imperative to ensure that teachers are furnished with adequate resources, subject enhancement strategies, and structured training sessions.